Now the IGOs get together - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Organising a revival in West Africa s agricultural fortunes is the shared agenda of more than twelve inter-governmental organisations (IGO) in the region. Their April 2001 meeting in Dakar, Senegal, also attended by CTA, concluded that for...